PENGARUH POST CURING TIME TERHADAP PERBEDAAN KEKERASAN, DIAMETRALTENSILE STRENGTH DAN WATER SORPTION: (KAJIAN TERHADAP BAHAN RESIN KOMPOSIT 3D PRINTING) - Joseph, Joseph; Dwisaptarini, Ade Prijanti; Melaniwati, Melaniwati; Tjandrawinata, Rosalina (Poltekkes Kemenkes Bandung, 2025)
Teeth that have undergone endodontic treatment often lose significant structure, requiring strong and durable restorations to prevent clinical failure and support long-term function. This study aimed to evaluate the effect of post-curing time on the hardness, diametral tensile strength (DTS), and water sorption of 3D-printed resin composites. An experimental study was conducted using 80 disc-shaped resin composite specimens divided into four groups based on post-curing time duration (5 minutes, 10 minutes, no curing, and control). Hardness was measured using the Vickers Hardness test, DTS with a Universal Testing Machine, and water sorption through immersion in artificial saliva. Hypothesis testing was performed using ANOVA and Post Hoc Tamhane tests. The results showed that increasing the post-curing time significantly improved hardness but did not affect DTS and water sorption. The group with 10 minutes of post-curing time achieved the best results in hardness improvement. The findings indicate that post-curing time positively influences the mechanical and physical properties of resin composites, particularly the hardness of 3D-printed materials. This process enables better polymer densification, resulting in stronger materials resistant to degradation in the oral environment. The duration of post-curing time significantly contributes to optimizing the mechanical and physical properties of 3D-printed resin composites, making it an essential step in manufacturing restorations for the long-term success of dental restorations.